The Roles of Regional Organisations in Strengthening Health Research Systems in Africa: Activities, Gaps, and Future Perspectives - Catherine Jones; Joëlle Sobngwi-Tambekou; Rhona Mijumbi; Aaron Hedquist; Clare Wenham; Justin Parkhurst (Kerman University of Medical Sciences, 2022)
Background  Regional cooperation on health in Africa is not new. The institutional landscape of regional cooperation for health and health research, however, has seen important changes. Recent health emergencies have focussed regional bodies' attention on supporting aspects of national health preparedness and response. The state of national health research systems is a key element of capacity to plan and respond to health needs - raising questions about the roles African regional bodies can or should play in strengthening health research systems.Methods  We mapped regional organisations involved in health research across Africa and conducted 18 interviews with informants from 15 regional organisations. We investigated the roles, challenges, and opportunities of these bodies in strengthening health research. We deductively coded interview data using themes from established pillars of health research systems - governance, creating resources, research production and use, and financing. We analysed organisations' relevant activities in these areas, how they do this work, and where they perceive impact.Results  Regional organisations with technical foci on health or higher education (versus economic or political remits) were involved in all four areas. Most organisations reported activities in governance and research use. Involvement in governance centred mainly around agenda-setting and policy harmonisation. For organisations involved in creating resources, activities focused on strengthening human resources, but few reported developing research institutions, networks, or infrastructure. Organisations reported more involvement in disseminating than producing research. Generally, few have directly contributed to financing health research. Informants reported gaps in research coordination, infrastructure, and advocacy at regional level. Finally, we found regional bodies' mandates, authority, and collaborations influence their activities in supporting national health research systems.Conclusion  Continued strengthening of health research on the African continent requires strategic thinking about the roles, comparative advantages, and capability of regional organisations to facilitate capacity and growth of health research systems.